2010
DOI: 10.1007/s11207-010-9643-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 3D Trajectories of Knots in Solar Prominences Using MSDP Data

Abstract: In this paper we present a new method of restoration of the true three-dimensional (3D) trajectories of prominence knots using ground-based observations taken with a single telescope that is equipped with a Multi-Channel Subtractive Double Pass imaging spectrograph. Our method allows us to evaluate the true 3D trajectories of the prominence knots without any assumptions concerning the shape of the trajectories or the dynamics of the motion. The reconstructed trajectories of several knots observed in three prom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In particular, filament altitude maps similar to those derived by Gissot et al (2008) with STEREO data were also derived by Schwartz et al (2004), hence prior to STEREO, even if the spectroscopic model developed by Schwartz et al (2004) requires much stronger assumptions on unknown quantities with respect to the Gissot et al (2008) analysis. Also, 3D trajectories of prominences similar to those derived by Bemporad (2009) andLiewer et al (2009) with the ''tie-pointing'' technique applied to STEREO data are mainly analogous to trajectories inferred by Zapiör and Rudawy (2007) by combining Ha images and spectra.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In particular, filament altitude maps similar to those derived by Gissot et al (2008) with STEREO data were also derived by Schwartz et al (2004), hence prior to STEREO, even if the spectroscopic model developed by Schwartz et al (2004) requires much stronger assumptions on unknown quantities with respect to the Gissot et al (2008) analysis. Also, 3D trajectories of prominences similar to those derived by Bemporad (2009) andLiewer et al (2009) with the ''tie-pointing'' technique applied to STEREO data are mainly analogous to trajectories inferred by Zapiör and Rudawy (2007) by combining Ha images and spectra.…”
Section: Discussionmentioning
confidence: 58%
“…An interesting technique to reconstruct the 3D trajectories of erupting prominence blobs has been recently developed by Zapiör and Rudawy (2007). In particular, the authors performed a numerical 3D trajectory reconstruction by analyzing Ha images and spectra acquired by a ground-based Multi-Channel Subtractive Double Pass spectrometer of the Astronomical Institute of the Wroclaw University (see also Rudawy et al, 2003).…”
Section: Eruptive Prominencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute starting positions of the knots along the Z -axis could not be determined with our method and thus we assumed for each knot z = 0 for starting or ending position. The detailed description of the applied reduction procedures was discussed in Zapiór and Rudawy (2010). The present version of the code automatically follows the positions of the selected knots on consecutive images, using simple knot identification and a tracking algorithm, which takes into account instantaneous changes of the brightness, shape and seeing-induced distortions of the knots.…”
Section: Observations and Data Processingmentioning
confidence: 99%
“…Thus, each opportunity for independent check of the obtained results should be explored. In our previous paper (Zapiór and Rudawy, 2010) we presented in detail a method of restoration of the true 3D trajectories of prominence knots using ground-based observations taken with a single telescope equipped with a Multi-channel Subtractive Double Pass (MSDP) imaging spectrograph (Mein, 1977). We have shown that the method allows an evaluation of the true 3D trajectories of the prominence knots without any assumptions concerning the shape of trajectories or dynamics of the motion.…”
Section: Introductionmentioning
confidence: 99%